2019
DOI: 10.1088/1361-6668/aaf61f
|View full text |Cite
|
Sign up to set email alerts
|

Development of sputtered Nb3Sn films on copper substrates for superconducting radiofrequency applications

Abstract: Superconducting radiofrequency (SRF) cavities that could provide a higher quality factor as well as a higher operational accelerating gradient at an affordable cost are in high demand for the future generation of particle accelerators. This study aims to demonstrate the potential of Nb3Sn as material of choice for such SRF applications. Due to its brittle nature, the only way to produce an Nb3Sn SFR cavity is to synthesise a thin layer inside a cavity made of niobium or copper. In this work, direct current mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…The experiments of Nb/Sn multilayers on oxidized Si and sapphire showed that, Nb 6 Sn 5 phase was present during the growth of A15 Nb 3 Sn. The Nb 6 Sn 5 phase disappeared above 800 • C. In this study, the highest T c of 17.45 K was observed for films annealed at 850 • C. Nb 3 Sn sputtered on copper [13,18,19] and Nb [20,21] substrates were studied for its application in SRF cavities. For Nb 3 Sn deposited on copper, the annealing temperature was limited to 830 • C due to a lower melting point of copper and the mismatch between the thermal expansion coefficients of copper and Nb 3 Sn [13].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The experiments of Nb/Sn multilayers on oxidized Si and sapphire showed that, Nb 6 Sn 5 phase was present during the growth of A15 Nb 3 Sn. The Nb 6 Sn 5 phase disappeared above 800 • C. In this study, the highest T c of 17.45 K was observed for films annealed at 850 • C. Nb 3 Sn sputtered on copper [13,18,19] and Nb [20,21] substrates were studied for its application in SRF cavities. For Nb 3 Sn deposited on copper, the annealing temperature was limited to 830 • C due to a lower melting point of copper and the mismatch between the thermal expansion coefficients of copper and Nb 3 Sn [13].…”
Section: Introductionmentioning
confidence: 82%
“…The Nb 6 Sn 5 phase disappeared above 800 • C. In this study, the highest T c of 17.45 K was observed for films annealed at 850 • C. Nb 3 Sn sputtered on copper [13,18,19] and Nb [20,21] substrates were studied for its application in SRF cavities. For Nb 3 Sn deposited on copper, the annealing temperature was limited to 830 • C due to a lower melting point of copper and the mismatch between the thermal expansion coefficients of copper and Nb 3 Sn [13]. Niobium has a high melting point and a thermal expansion coefficient close to that of Nb 3 Sn [22].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Among the different intermetallic phases of the Nb-Sn system, only the A15-type Nb 3 Sn is superconducting above 10 K. However, thin film synthesis of high quality Nb 3 Sn is still a huge challenge. 2 Among the reported thin film deposition methods are tin evaporation, [3][4][5] chemical vapor deposition, 6 sputtering, [7][8][9][10][11] electron beam evaporation, 12 bronze processing, 13 and electrodeposition. 14 However, the tin diffusion process is the only process used so far for the production of cavities.…”
Section: Introductionmentioning
confidence: 99%
“…Various technique have been developed to grow Nb 3 Sn superconductor. Bronze routes, sputtering techniques, tin dip et cetera have been studied (see [7][8][9][10] and references therein), but require further development due to the exceptional quality of the RF surface necessary to sustain high RF fields. The best Nb 3 Sn-coated SRF cavities so far have been produced with the so-called vapor diffusion process [11].…”
Section: Introductionmentioning
confidence: 99%